Disturbance, microclimate and historical habitat connectivity determine the population performance of the threatened grassland specialist Carex caryophyllea in remnant grasslands - Jussi Lampinen (John Wiley & Sons, 2025)
Many grassland specialist plant populations in Europe have become restricted to remnant habitats. The performance of these populations depends on both species-specific traits and local and landscape level aspects of habitat quality. Understanding which specific local or landscape level conditions determine the performance of grassland species populations in remnant habitats would help design the restoration of the habitats and to detect the conditions that favour the long-term persistence of grassland species in them. Such information is especially needed in urbanised landscapes, where remnant habitats engulfed by urban land use types may experience increased erosion, higher temperatures and invasion by alien species. This study investigates the population performance determinants of Carex caryophyllea (VU), a grassland specialist, in 43 remnant grasslands in an urban-rural gradient in Finland. The population performance was assessed with metrics of persistence, establishment and reproduction, and related to environmental conditions with generalized additive models and redundancy analysis. The most important positive determinants for the performance of C. caryophyllea populations were disturbance through management or ground erosion, a warm microclimate, large habitat area and high historical connectivity to suitable grassland habitats. Present connectivity to other C. caryophyllea populations had a weak and near-significant positive relationship with population performance. Urbanisation of the surrounding landscape correlated with population performance as well, possibly due to the high historical cover of grasslands in presently urbanised landscapes. The results imply that the most effective restoration method of remnant C. caryophyllea populations would be reinstating disturbance regimes in overgrown habitats with warm microclimates close to suitable habitats and other existing populations, whether urban or rural. This would counteract the species' future decline due to possible extinction debts and help the species persist in the study area in the long term.